2022
DOI: 10.3390/jcm11226618
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cytokine Levels during Normothermic Kidney Perfusion with Whole Blood- or Red Blood Cell-Based Perfusates—Results of a Scoping Review and Experimental Study

Abstract: The ideal composition of the perfusate for normothermic kidney perfusion is unknown, though the perfusate commonly used to perfuse human kidneys contains leukocyte-depleted packed red blood cells (RBC), as this is believed to prevent excessive inflammation. We performed a systematic search identifying 19 articles reporting on cytokine levels during normothermic pig or human kidney perfusion. Cytokine levels varied widely across the reported studies. No direct comparisons of perfusate cytokines during perfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Although not the study’s focus, we found no clear evidence suggesting whole blood perfusion, commonly though, to lead to increased inflammation and injury because of white cells and platelets, is worse than RBC perfusion. We reported earlier that little evidence suggests a difference in perfusate cytokine concentrations between whole blood and RBC perfusions which might explain similar clinical read-outs 43 . Tissue-resident immune cells, abundantly present in the kidney, are released in the perfusate during normothermic perfusion, and these likely play a part in the observed inflammatory response 44–46 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although not the study’s focus, we found no clear evidence suggesting whole blood perfusion, commonly though, to lead to increased inflammation and injury because of white cells and platelets, is worse than RBC perfusion. We reported earlier that little evidence suggests a difference in perfusate cytokine concentrations between whole blood and RBC perfusions which might explain similar clinical read-outs 43 . Tissue-resident immune cells, abundantly present in the kidney, are released in the perfusate during normothermic perfusion, and these likely play a part in the observed inflammatory response 44–46 …”
Section: Discussionmentioning
confidence: 96%
“…We reported earlier that little evidence suggests a difference in perfusate cytokine concentrations between whole blood and RBC perfusions which might explain similar clinical read-outs. 43 Tissue-resident immune cells, abundantly present in the kidney, are released in the perfusate during normothermic perfusion, and these likely play a part in the observed inflammatory response. [44][45][46]…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-6 levels need to be interpreted cautiously, as it has both pro- and anti-inflammatory properties [ 40 , 41 , 42 ]. Recently, De Beule et al found that the cytokine levels between kidneys perfused with whole blood and those perfused with pRBCs did not differ significantly [ 43 ]. As pRBCs are deprived of leukocytes, one would assume that the inflammatory response is milder in comparison to whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review by De Beule et al found that during machine perfusion, perfusate cytokine levels are similar in kidneys perfused with whole blood compared to kidneys perfused with leukocyte-depleted packed red blood cells [142]. This demonstrates that kidney tubular epithelial cells and the resident immune cells can produce large amounts of cytokines and chemokines, which can upregulate inflammatory pathways within the graft before implantation and independently of the presence of an immune system.…”
Section: Targeting Inflammatory Pathways and The Immune Systemmentioning
confidence: 99%